Modern problems of fire safety in the forests of the "Svyati Gory" NPP - Melnyk, E. E.; Sydorenko, S. H.; Koval, I. M.; Voron, V. P. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The publication highlights the current problems of forest fire safety in the front-line territories of the Donetsk region of Ukraine, which are the most dangerous due to Russia's hostilities, and based on our past scientific research, further negative changes in the fire-damaged areas of pine forests are modeled. As an example, a part of the territory of the nature reserve fund of the Donetsk region was used, namely the "Svyaty gory " NNP, which was particularly badly affected by this year's large-scale fires with an area of several thousand hectares. Not only the main current impact of such forest fires is analyzed, but the importance of forecasting the further consequences of vegetation changes on the fires in the following years is shown.